Implementing Canva in a Flipped Classroom: A Challenge in Post Pandemic Era - Kiswati; Mohammad Kunsarwani (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2022)
In post pandemic era, schools are allowed to invite students to face-to-face learning. Despite this, most teachers still suffer from a lack of time since the government still uses limited time at schools, referred to as “PTM terbatas”. This research used a descriptive quantitative design. It aimed to investigate the students’ interest in the use of Canva in improving their mastery of brochures/pamphlets/banners/posters in the eleventh grade at MAN 5 Jombang. There are more than 100 students involved in this research. To address the problem of lack of time in this post-pandemic era, the teacher employed the Flipped Classroom model. According to the findings, the students are satisfied with the use of Canva, preferring it to paper and finding it useful in accomplishing the task. As a result of using Canva in a flipped classroom, the teacher has also been able to effectively manage her limited time at school. Based on the result of this research, it can be concluded that Canva combined with Flipped Classroom model is suggested to be used in this post-pandemic era to answer the challenge of digital technology in this disruptive era. Keywords: Canva, Flipped Classroom Model, Post Pandemic Era